2015
DOI: 10.1002/2014gl062447
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal Pacific variability and eastern Australian megadroughts over the last millennium

Abstract: The Interdecadal Pacific Oscillation (IPO) influences multidecadal drought risk across the Pacific, but there are no millennial-length, high-resolution IPO reconstructions for quantifying long-term drought risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
187
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(196 citation statements)
references
References 45 publications
9
187
0
Order By: Relevance
“…Barring post-depositional processes, the recorded snow accumulation is the net result of solid precipitation, sublimation, wind erosion or deposition, and meltwater runoff. Integrated over the AIS the contributions made by sublimation or deposition, wind redistribution, rainfall, and meltwater runoff are relatively small (van Wessem et al, 2014) and therefore the dominant component of Antarctic SMB is solid precipitation. Locally, however, drifting snow erosion or deposition and sublimation may play an important role, especially in regions of strong katabatic flow .…”
Section: Snow Accumulation From Ice Coresmentioning
confidence: 99%
See 4 more Smart Citations
“…Barring post-depositional processes, the recorded snow accumulation is the net result of solid precipitation, sublimation, wind erosion or deposition, and meltwater runoff. Integrated over the AIS the contributions made by sublimation or deposition, wind redistribution, rainfall, and meltwater runoff are relatively small (van Wessem et al, 2014) and therefore the dominant component of Antarctic SMB is solid precipitation. Locally, however, drifting snow erosion or deposition and sublimation may play an important role, especially in regions of strong katabatic flow .…”
Section: Snow Accumulation From Ice Coresmentioning
confidence: 99%
“…A recent evaluation of 3265 multiyear averaged in situ observations concluded that ERA-Interim exhibits the highest performance in capturing interannual variability in observed Antarctic precipitation of the available reanalysis products (Wang et al, 2016). In addition, we use the latest version of RACMO version 2.3p2 (RACMO2.3p2), which succeeds RACMO2.3 (Van Wessem et al, 2014) and combines the hydrostatic dynamics of the High Resolution Limited Area Model (HIRLAM) with the physics package of the ECMWF Integrated Forecast System. RACMO2.3p2 has been specifically adapted for use over glaciated regions, as it is coupled to a multilayer snow model (Ettema et al, 2010) that calculates processes in the firn, such as grain size growth, firn compaction, meltwater percolation or retention, and meltwater runoff.…”
Section: Modelled Surface Mass Balancementioning
confidence: 99%
See 3 more Smart Citations